2011
DOI: 10.3174/ajnr.a2455
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Findings in the Reticular Formation in Siblings withMPV17-Related Mitochondrial Depletion Syndrome

Abstract: SUMMARY:Hepatocerebral MPV17-MDS is quite rare (Ͻ30 confirmed cases), with limited findings described on MR imaging. We report 2 siblings having abnormalities within the reticular formation of the lower brain stem and within the reticulospinal tracts at the cervicocranial junction on T2WI. The presence of these MR imaging findings (relative to previous reports) raises the possibility that they represent subtle but characteristic findings corresponding to clinically observed abnormalities of tone encountered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Approximately 30 affected individuals have been reported with MPV17-related hepatocerebral MDS [59][60][61][62][63][64][65][66][67][68]. Of note, among those confirmed cases are individuals with Navajo neurohepatopathy who were found to have homozygous p.Arg50Gln mutations in MPV17.…”
Section: Mpv17-related Hepatocerebral Mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 30 affected individuals have been reported with MPV17-related hepatocerebral MDS [59][60][61][62][63][64][65][66][67][68]. Of note, among those confirmed cases are individuals with Navajo neurohepatopathy who were found to have homozygous p.Arg50Gln mutations in MPV17.…”
Section: Mpv17-related Hepatocerebral Mdsmentioning
confidence: 99%
“…Less frequent manifestations include renal tubulopathy, hypoparathyroidism, and gastrointestinal dysmotility that manifests as gastroesophageal reflux, cyclic vomiting, and diarrhea. Corneal anesthesia and ulcers were reported in individuals homozygous for the mutation p.Arg50Gln [59][60][61][62][63][64][65][66][67][68].…”
Section: Mpv17-related Hepatocerebral Mdsmentioning
confidence: 99%
“…3 To date, MDS caused by MPV17 mutations has been reported in 32 patients with the clinical manifestations including early progressive liver failure, neurological abnormalities, hypoglycaemia and raised blood lactate. 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 Recently, MPV17 mutations have also been associated with autosomal recessive adult-onset neuropathy and leukoencephalopathy with multiple mtDNA deletions in skeletal muscle. 16 Thus, as for POLG , RRM2B and TK2 , MPV17 mutations can lead to recessive MDS or recessive multiple mtDNA deletion disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Besides hepatic and neurologic indications, hepatocerebral MDDS can result in metabolic manifestations, such as lactic acidosis and hypoglycemia, and it has frequently been observed that patients fail to thrive. Additional, less commonly noticed features are described in detail elsewhere (Karadimas et al, 2006;Spinazzola et al, 2006Spinazzola et al, , 2008Wong et al, 2007;NavarroSastre et al, 2008;Kaji et al, 2009;Parini et al, 2009;El-Hattab et al, 2010;Merkle et al, 2012;Uusimaa et al, 2013). Remarkably, the identical mutation might cause different severity, onset and pathology in different patients, as Blakely et al describe a patient with adult-onset of neuropathy and leukoencephalopathy, carrying a homozygous mutation (P98L) described in infantile MDDS syndrome previously (El-Hattab et al, 2010;Blakely et al, 2012).…”
Section: Human Mpv17-related Diseasementioning
confidence: 95%
“…Hepatic and neurologic manifestations appear to be the most characteristic findings. All early-onset patients studied presented with liver dysfunction, comprising cholestasis, jaundice and coagulopathy (see Karadimas et al, 2006;Spinazzola et al, 2006Spinazzola et al, , 2008Wong et al, 2007;Navarro-Sastre et al, 2008;Kaji et al, 2009;Parini et al, 2009;El-Hattab et al, 2010;Merkle et al, 2012;Uusimaa et al, 2013). Patients developing cirrhosis or hepatocellular carcinoma were described less frequently (see Karadimas et al, 2006;El-Hattab et al, 2010).…”
Section: Human Mpv17-related Diseasementioning
confidence: 99%